Integration of Building Information Modelling (BIM) in Civil Engineering Project: A Literature Review - Sugeng Purwanto; Tri Satriawansyah (AKADEMI TEKNIK ADI KARYA, 2025)
Building Information Modelling (BIM) has revolutionized the construction industry by presenting a new approach to project design and construction. BIM enables the integration of comprehensive project data, including 3D design, material information, and construction schedules, into a centralized digital model. This literature review aims to explore the integration of BIM in civil engineering projects, focusing on its benefits, challenges, and implementation. This study aims to examine the integration of Building Information Modelling (BIM) in civil engineering projects through a comprehensive literature review. BIM is a technology that enables the creation and management of digital representations of the physical and functional characteristics of a construction project. The results of this study conclude that BIM enables more accurate and efficient design by detecting potential clashes and design errors in the early stages of the project thus saving time and costs.